AGORA EU, CORPO, SINTO, PENSO E EVIDENCIO – A PRESENÇA DO DUALISMO E RACIONALISMO NA EDUCAÇÃO - C., Celeste Pánik (2009)
This research has as central focus the study about the situation of the body aspect and the human movement in the Brazilian educational system. To develop this thematic had been used three big pillars of different knowledge areas, but articulated between them; they are: Philosophy, Physical Education and Education. From a philosophical vision, they had been analyzed many subjects about the body and the situation of this one with the educational structures that exists, using especially the actual condition of Physical Education at School as support to accomplish this analysis. Having as an initial base the dualism and the rationalism represents the structural base of the educational scope, from this point, happen an increase in the reduction of the importance of the body and its movement in the educational structures was made reflections and discussions during the work development. Described for bibliographical and documentary survey, with description, exploration and analysis of official documents of the Brazilian education and endorsed by the authors of the reference from the related areas, this research presents a development of ideas that converge as much for the overcoming dualist human being vision, (that divides in opposing and not transposable polar regions body and soul, body and mind), as for a system that praises the full human development.(AU)